Epidémiological Aspects and Factors Associated with Early Neonatal Death From 2018 to 2020 in the Maternity of the Savè-Ouessè Health Zone, Bénin, West Africa - AGUEMON, BADIROU DIN OWOLADÉ OTONIKOU; DAMIEN, Georgia (My University, 2023)
Background: Most of the new-born deaths occur in developing countries where care access is poor. This study aimed to investigate the epidemiological aspects and factors associated with early neonatal death in maternity of the Savè-Ouessè health zone in the Collines department in Benin. Subjects and Method: A case-control study was conducted from 2018 to 2020. Two groups of new-borns aged 0-7 days were recruited, 176 cases and 176 controls. Data were entered and analysed using SPPS software version 28.0.1. Logistic regression model was used to identify factors that explain early neonatal death occurrence. Results: The early neonatal mortality rate was 7.03‰ and all deaths occurred within the first 24 hours after delivery. Analysis after adjustment had identified lack of desire for motherhood (ORa=3.219); lack of active fetal movements (ORa=7.015); no observance of ANC rhythm (ORa=5.145) ; lack of sulfadoxine-pyrimethamine intake (ORa=6.336); insufficient SP intake (ORa=1.979); stained or meconium amniotic fluid (ORa=1.171); cloudy amniotic fluid (ORa=2.659); heme amniotic fluid (ORa=4.091) as factors that increased the occurrence of early neonatal mortality. Conclusion: Even if early neonatal mortality appears to be low in the Savè-Ouessè health zone, its reduction requires to strengthen family planning, to improve the observance of intermittent preventive treatment and to monitor obstetric labour. Keywords: perinatal death, early neonatal, death, associated factors, Benin
Keywords: Périnatal death; early neonatal; death; associated factors; Bénin